PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM MENGKATALISASI KREATIVITAS SISWA DI ERA DIGITAL - Jhoni Hardori; April Penu; Akdes Johanis Siregar; Ebenezer Hutasoit; Olivia Durikasi (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
Student creativity in schools is something that must continue to be explored. A Christian Religious Education teacher must encourage every student to compete in the global world. However, students sometimes find it difficult to discover their potential. Therefore, a teacher acts as a guide to develop a student's creativity. The method here is used using the literature study research method to find the data obtained. Then a descriptive qualitative approach, the data is presented in narrative form. The results of this research found that a Christian religious education teacher can develop students' creativity through vlogs and podcasts where they can be maximally creative in learning Christian religious education, not only focusing on writing but digitalization.